The IDA pro book : the unofficial guide to the world's most popular disassembler - Eagle, Chris (No Starch Press, 2011)
IDA Pro is a commercial disassembler and debugger used by reverse engineers to dissect compiled computer programs, and is the industry standard tool for analysis of hostile code. The IDA Pro Book provides a comprehensive, top-down overview of IDA Pro and its use for reverse engineering software. Author Chris Eagle, a recognized expert in the field, takes readers from the basics of disassembly theory to the complexities of using IDA Pro in real-world situations. Topics are introduced in the order most frequently encountered, allowing experienced users to easily jump in at the most appropriate point. Eagle covers a variety of real-world reverse engineering challenges and offers strategies to deal with them, such as disassembly manipulation, graphing, and effective use of cross references. This second edition of The IDA Pro Book has been completely updated and revised to cover the new features and cross-platform interface of IDA Pro 6.0. Other additions include expanded coverage of the IDA Pro Debugger, IDAPython, and the IDA Pro SDK.